Asylum seekers: How attributions and emotion affect Australians' views on mandatory detention of " the other" - Hartley, Lisa; Pedersen, Anne (Australian Psychological Association, 2007)
There is little research regarding the social psychological processes shaping community opinions about asylum seeker policy. Here, we explored two issues by way of a random community survey of the Perth metropolitan area. We first examined whether the intergroup perceptions that occur when individuals focus upon the Australian community (self-focus) or asylum seekers themselves (other-focus) when evaluating the issue of asylum seekers in detention affected community opinions. Regarding self-focus, perceiving the Australian community as stable (not seeing asylum seekers as a threat to the stability of Australian society) predicted a more lenient policy orientation, as did perceiving the government's policy as illegitimate. Regarding other-focus, perceiving asylum seekers as legitimate, their situation in detention as unstable, and empathy predicted a more lenient policy orientation. Second, we examined the accuracy with which participants estimated wider community consensus for their respective policy orientation. As predicted, over-estimation increased as participants favoured tougher policy.